The Determinants of Tax Evasion in Gombe State Nigeria - Mansor, Muzainah; Gurama, Zakariya’u (International Journal of Economics and Financial Issues, 2016)
Tax evasion is among the major societal problems inhibiting development in developing countries. Literature exposes that tax evasion also denote some of the difficulties in raising revenue in Nigeria. This study assessed the determinants of tax evasion in Gombe State (a state in Nigeria). The study was conducted through a survey research design. A questionnaire was used to gather primary data from 303 randomly selected public and private sector personal taxpayers in Gombe. The results of the analysis show that tax system, income level and education level have significant positive relationship with tax evasion. On the other hand, tax rate and corruption have positive but insignificant relationship with tax evasion. This study recommends that necessary measures should be taken by the tax authority to improve revenue collection and reduce tax evasion. It is also proposed that campaign against corruption, public enlightens on tax matters and revision of tax processes should be undertaken. Keywords: Tax evasion, Gombe State, Nigeria. JEL Classification: H26